OBSTACLE OF COVID-19 DIGITAL SURVEILLANCE AT PUBLIC HEALTH CENTERS: EXPLORATORY STUDY IN WEST JAVA: Hambatan Surveillans Digital COVID-19 pada Pusat Kesehatan Masyarakat: Studi Explorasi di Jawa Barat - Heriana, Cecep; Binti Moh Said, Faridah; Yasmin, Farzana (Jurnal Berkala Epidemiologi, 2024)
Background: The quality of COVID-19 data from surveillance information systems is still an issue in low-middle-income countries (LMIC), including Indonesia, which uses various applications that have the potential to affect surveillance performance. Purpose: To explore the procedures and obstacles to using various digital surveillance applications at Public Health Centers (PHCs) in Indonesia. Methods: Qualitative research with exploratory studies was used.  The setting was in the PHC in Kuningan, Majalengka, and Indramayu, City of Cirebon, Indonesia, with surveillance officer participants and contact tracer data manager, as many as 8.  Data was collected by interviewing and using snowball sampling techniques between May 12 and 20, 2022. Data were analyzed using content analysis. Results: The initial data collection procedure involves obtaining data from various health facilities.  Data recording was with SILACAK and the New All-Recorded application.  Data analysis with descriptive epidemiology was reported to the head.  Data quality was achieved with monitoring.  Obstacles in data collection were rejection, community paradigm, and fear. The obstacles of the application are maintenance, not immediately updating that day, not entering at that time, sometimes it does not run smoothly, there are no tools for visualization, and data distribution per place not yet available. Conclusion: In COVID-19 surveillance procedures, from initial data collection, data recording, data analysis, data reporting, and data quality assurance, there are obstacles to data collection in the community and to applications used for surveillance. The District Health Office must compile new procedures that include data management stages, epidemiological data analysis, and visualization.